Persuasive Language In Skintific Advertisements On Instagram: A Semantics Analysis - Desfita Desfita; Helmita Helmita (Jurnal Ilmiah Pendidikan Scholastic, 2025)
This research is entitled "Persuasive Language in Skintific Advertisements on Instagram: A Semantic Analysis". The purpose of this research is to identify persuasive language in Skintific advertisements on Instagram posts. The category of persuasive language refers to Lamb's theory (2019), using a qualitative descriptive method. The researcher collected ninety-six Skintific advertisement data from Instagram posts. The data was then analyzed by categorizing and interpreting it into the appropriate categories. The results of the research and discussion show that out from 96 Skintific advertisement data on Instagram posts, 65 data were found. These data are categorized as follows: 4 Alliteration, 9 Appeals, 2 Connotation, 18 Emotive Language, 6 Colloquial Language, 2 Hyperbole, 1 Expert Opinion, 6 Inclusive Language, 7 Imagery, 6 Jargon, 3 Rhetorical Questions and 1 Simile. The most common persuasive language used in Skintific advertisement on Instagram posts is Emotive Language, as Skintific frequently employs language that evokes an emotive response from readers or listeners. Skintific aims to show similar emotions and preferences to its consumers and boost confidence, motivating them to achieve good results.